2021
DOI: 10.21009/spektra.061.05
|View full text |Cite
|
Sign up to set email alerts
|

MODIFICATION OF PURUN TIKUS (ELEOCHARIS DULCIS) AS A NATURAL FIBER COMPOSITE USING KMnO4 AND NaOH

Abstract: The choice of natural fibers as a composite reinforcing material is related to the advantages of being cheap, abundant, renewable, and environmentally friendly. This research was conducted to study the effect of de-lignification treatment on the properties of purun tikus (Eleocharis Dulcis) fiber. Purun tikus fiber has been modified with the alkaline treatment of KMnO4 2% and NaOH 5%. This treatment was mainly applied to improve the physical and chemical properties of purun tikus fiber. Changes in chemical cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 9 publications
0
15
1
Order By: Relevance
“…This is in accordance with the purpose of the treatment, which is to isolate cellulose from lignin and hemicellulose. The hemicellulose content of short fiber purun tikus with 5% NaOH treatment for three hours was 0.97% [3], while in this study, the hemicellulose content of long fiber with the 5% NaOH treatment was 0.33%. This value is smaller than in previous studies.…”
Section: Resultscontrasting
confidence: 50%
See 4 more Smart Citations
“…This is in accordance with the purpose of the treatment, which is to isolate cellulose from lignin and hemicellulose. The hemicellulose content of short fiber purun tikus with 5% NaOH treatment for three hours was 0.97% [3], while in this study, the hemicellulose content of long fiber with the 5% NaOH treatment was 0.33%. This value is smaller than in previous studies.…”
Section: Resultscontrasting
confidence: 50%
“…Analysis of lignin content showed that the hot water immersion treatment and 5% NaOH treatment had reduced the lignin content of the purun tikus fiber. Haryanti [3] stated that the lignin content in the purun tikus short fiber without treatment was 45.03%. Based on Table 2, both treatments succeeded in reducing the lignin content in the fiber, but the NaOH treatment was the best treatment in reducing the lignin content in the purun tikus fiber.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations